2021
DOI: 10.1038/s41437-021-00450-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-step genomic prediction of Eucalyptus dunnii using different identity-by-descent and identity-by-state relationship matrices

Abstract: Genomic selection based on the single-step genomic best linear unbiased prediction (ssGBLUP) approach is becoming an important tool in forest tree breeding. The quality of the variance components and the predictive ability of the estimated breeding values (GEBV) depends on how well marker-based genomic relationships describe the actual genetic relationships at unobserved causal loci. We investigated the performance of GEBV obtained when fitting models with genomic covariance matrices based on two identity-by-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 69 publications
(104 reference statements)
5
16
0
Order By: Relevance
“…However, the dispersion of pair-wise relationship coefficients of ssGBLUP-IBD is lower than the ssGBLUP-IBS model ( Table 4 ). While the high heritability of ssGBLUP-IBS, low dispersion of relationship coefficients of ssGBLUP-IBD and high prediction accuracy of ssGBLUP-IBD model are similar to the results of Jurcic et al (2021) , there is however no difference between the two models in predictive ability with both GBLUP ( Figure 1 ) and ssGBLUP ( Figure 4 ). The discrepancy in the performance of the models with IBD in the current study and the previous study may be due to the type of population and the type of markers used in the two studies.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, the dispersion of pair-wise relationship coefficients of ssGBLUP-IBD is lower than the ssGBLUP-IBS model ( Table 4 ). While the high heritability of ssGBLUP-IBS, low dispersion of relationship coefficients of ssGBLUP-IBD and high prediction accuracy of ssGBLUP-IBD model are similar to the results of Jurcic et al (2021) , there is however no difference between the two models in predictive ability with both GBLUP ( Figure 1 ) and ssGBLUP ( Figure 4 ). The discrepancy in the performance of the models with IBD in the current study and the previous study may be due to the type of population and the type of markers used in the two studies.…”
Section: Discussionsupporting
confidence: 70%
“…In a recent study, Jurcic et al (2021) have shown that implementation of a ssGBLUP with IBD relationship matrix resulted in better performance compared to a ssGBLUP model with IBS GRM in E. dunnii . Higher predictive ability was observed with IBD compared to the IBS matrix for DBH and stem straightness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, that is not a major concern if SNP arrays are applied to screen populations that are genetically related to the resequencing panels. SNP arrays have proven particularly useful for genome-informed breeding applications, such as checking sample identity, pedigree and relationship assignment, trait mapping and genomic predictions [9][10][11][12][13][14]. Nonetheless, when applying SNP arrays to screen wild/natural populations, increased attention needs to be given to the possibility that genetic variation can be missed.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been a number of studies applying this “HBLUP” approach to forest tree populations (e.g. Ratcliffe et al 2017 ; Klápště et al 2018 ; Thavamanikumar et al 2020 ; Ukrainetz and Mansfield 2020 ; Callister et al 2021 ; Jurcic et al 2021 ), none have yet considered multiple base populations such as provenances.…”
Section: Introductionmentioning
confidence: 99%